Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s10620-010-1399-7
|View full text |Cite
|
Sign up to set email alerts
|

Can an Immunohistochemistry Method Differentiate Intestinal Tuberculosis from Crohn’s Disease in Biopsy Specimens?

Abstract: Immunohistochemical staining of biopsy specimens with anti-VP-M660 seems to be a simple and fast technique with 73% sensitivity and 93% specificity for establishing an earlier differentiation of M. tuberculosis from Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…We propose to carry out further work in developing a species-specific monoclonal antibody to Ag85B. As the expression level of Ag85B is much higher than that of PstS1, and the expression patterns of these two antigens are quite different, detection of Ag85B has an advantages in disclosing TB cases 19 21 22…”
Section: Discussionmentioning
confidence: 99%
“…We propose to carry out further work in developing a species-specific monoclonal antibody to Ag85B. As the expression level of Ag85B is much higher than that of PstS1, and the expression patterns of these two antigens are quite different, detection of Ag85B has an advantages in disclosing TB cases 19 21 22…”
Section: Discussionmentioning
confidence: 99%
“…Except for traditional histological examinations, surface markers identified by immunohistochemistry or immunofluorescence also contribute to the differential diagnosis between CD and ITB. Anti‐VP‐M660, a specific monoclonal antibody targeting the antigen of M. tuberculosis complex was reported to have a sensitivity of 73% and a specificity of 93% for the diagnosis of ITB . Banerjee and colleagues found that M. tuberculosis evaded host immunity by recruiting CD73 + mesenchymal cells around the granulomas, a process that is absent in CD.…”
Section: Histological Featuresmentioning
confidence: 99%
“…Anti-VP-M660, a specific monoclonal antibody targeting the antigen of M. tuberculosis complex was reported to have a sensitivity of 73% and a specificity of 93% for the diagnosis of ITB. 41 Banerjee and colleagues 42 found that M. tuberculosis evaded host immunity by recruiting CD73 + mesenchymal cells around the granulomas, a process that is absent in CD. Therefore, the identification of CD73 expression can also be used in a diagnostic differentiation.…”
Section: Histological Featuresmentioning
confidence: 99%
“…The identification of acid-fast bacilli on intestinal biopsies of ITB was 25–36% in the literature. 6,25–27 In the present cohort, all ITB specimens were negative for acid-fast staining. M. tuberculosis culture may take several weeks, resulting in delayed diagnostic confirmation and treatment initiation.…”
Section: Discussionmentioning
confidence: 57%